Hubungan Antara Dukungan Keluarga Dengan Tingkat Kepatuhan Pasien Dalam Perawatan Luka Post Operasi Debridement Di Rumah Sakit - Ariani, Sri Purwanti; Sri Jamilah; Ernawati, Ernawati; Wahyu Asnuriyati (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Family support plays an important role in improving patient compliance with wound care following debridement surgery. Patients who receive emotional support, information, and practical assistance from their families tend to adhere more closely to medical instructions, such as maintaining wound hygiene, changing dressings on schedule, and following healthcare providers’ recommendations. Factors such as attention, motivation, and active family involvement in the care process can enhance the patient’s comfort and confidence during recovery.